A Case–control Study of Haemorrhagic Septicaemia in Buffaloes and Cattle in Karachi, Pakistan, in 2012. Issue 2 (17th July 2015) - Moustafa, A. M.; Ali, S. N.; Bennett, M. D.; Hyndman, T. H.; Robertson, I. D.; Edwards, J.
Summary: A retrospective epidemiological case–control study was performed in Karachi, Pakistan, from January to April 2013. The owners of 217 dairy cattle and buffalo farms from six different locations in Karachi were interviewed. The aim of the study was to identify risk factors associated with the presence of haemorrhagic septicaemia (HS). Farms with a history of at least one instance of sudden death in a dairy animal during 2012 and a positive clinical HS diagnosis (made by local veterinarians) were defined as cases. Farms having no history of sudden deaths in 2012 were defined as controls. Univariable analyses were initially conducted, and factors with P ≤ 0.25 were offered to a multivariable logistic regression model to identify putative risk factors. The final multivariable logistic model contained five factors. Vaccination was found to be a protective factor (OR = 0.22) along with the length of time cattle were kept on farm (months). For every extra month cattle were kept, the odds of HS disease were reduced by a factor of 0.9. In contrast, for every extra animal in a herd, the risk of infection increased by a factor of 1.01. Supplying underground water and the presence of foot and mouth disease on the farm increased the risk by 2.90 and 2.37, respectively. To understand the epidemiology of HS in Karachi dairy herds, more in‐depth research is required to study the risk and protective factors identified in this survey and to evaluate risk mitigation strategies, where possible.